Meridional changes in water mass distributions off NW Africa during November 2007/2008 - Pastor, María V.; Peña Izquierdo, J.; Pelegrí Llopart, José Luis; Marrero-Díaz, A. (Ciencias Marinas, 2013)
An optimum multiparameter analysis was applied to a data set for the eastern boundary of the North Atlantic subtropical gyre,\ngathered during November of two consecutive years and spanning from 16 to 36º N. This data set covers over 20º of latitude with good\nmeridional and zonal resolution over the whole coastal transition zone. The contribution from six water types in the depth range between 100\nand 2000 m is solved. In the 100 to 700 m depth range the central waters of southern and northern origin meet abruptly at the Cape Verde\nFrontal Zone. This front traditionally has been reported to stretch from Cape Blanc, at about 21.5º N, to the Cape Verde Islands, but in our case\nit penetrates as far as 24º N over the continental slope. South of 21º N latitude we actually find a less saline and more oxygenated variety of\nSouth Atlantic Central Water, which we ascribe to less diluted equatorial waters. In the 700 to 1500 m depth range the dominant water type is a\ndiluted form of Antarctic Intermediate Water (AAIW), whose influence smoothly disappears north of the Canary Islands as it is replaced by\nMediterranean Water (MW); at latitudes where both water masses coexist, we observe MW offshore while AAIW is found near-shore. North\nAtlantic Deep Water is the dominating water type below about 1300/1700 m depth south/north of the Canary Islands; this abrupt change in\ndepth suggests the existence of different paths for the deep waters reaching both sides of the archipelago. 244 223 0,297 0,609 Q3 Q4 SCIE